Prototype Design of Radio Frequency Energy Harvesting for Lighting Applications - Rohana, Assa Kesthy; Djatmiko, Wisnu; Sandi, Efri; Pangestu, Agung; Al Hakim, Rosyid Ridlo (Journal of Global Engineering Research and Science, 2023)
The prototype resonant frequency is designed to work at 150 MHz. The signal source prototype is the signal that comes from handy talky (HT). There are two subsystems, which are Matching Impedance and Voltage Multiplier. The resonant frequency of the matching impedance subsystem at 143 MHz from 0.053 mH inductor and 0.0233 pF capacitor. The output of the matching impedance subsystem is then amplified by the multiplier voltage subsystem using parallel PH4148 diodes with the 6-stage multiplier. Load prototype is a CR-151 LED that works at 12 volts 1 watt. When the HT battery has a voltage of 7.3 volts, the prototype can turn on the lamp with the distance between the TX antenna and the antenna on the prototype less than 36 cm. The maximum voltage on the load is 6.8 volts with a length of 5 cm between the antenna and the lamp 774 lumen.